Study of thermal management system for battery box for formula student electric racing car - Han, Yawen; Bai, Yuxing; Zhang, Weixin; Cui, Song; Zang, Liguo; Ding, Hongshan (Frontiers in Mechanical Engineering, 2025)
In Formula Student Electric (FSE) racing competitions, battery overheating is a common challenge due to inadequate thermal dissipation at high discharge rates, negatively impacting the performance of the racing vehicle. This study introduces an innovative and optimized battery box cooling system designed to mitigate overheating by reducing the maximum battery temperature and the temperature gradient.The cooling system is developed using a combined approach of simulation analysis and orthogonal experiments. The design optimization focuses on improving airflow distribution by increasing the number of inlet and outlet vents and adjusting the airflow velocity, which enhances the heat dissipation capacity. Experimental tests show that, under a 5C discharge rate for 60 s, the maximum temperature within the optimized cooling system is reduced to 27.4°C. The temperature difference decreases from 3.5°C to 2.4°C, resulting in a 31.4% improvement in optimization efficiency. Additionally, the optimized system achieves a more uniform temperature distribution across the battery pack, outperforming the pre-optimization design in all evaluated metrics. The optimized cooling system demonstrates a significant improvement in thermal performance compared to the original design. The findings highlight the effectiveness of the proposed optimization in enhancing the thermal management of the battery box and offer a practical, applicable strategy for improving thermal efficiency in electric vehicle applications.